PSYCHOLOGICAL FACTORS DETERMINING LACK OF SEXUAL URGE AMONG FEMALE IN SOUTH-SOUTH - Gbaranor K. B; Imarhiagbe O. C; 2Nnadi N. O; Barinua-Gbaranor N. P; Biralo P. K; Mube W. A; Biibaloo L. L; Pepple, B. G; Ogbonda N. P; Mgbere M; John E. E; Etuk M. S; et al. (Western European Studies, 2025)
Sexual urge (libido) is a pre-determining factor and physiological process that occur before active sex and it is a driving force for sexual intercourse. Sexual urge is the feeling that you have, that gives you the desire for sex and without this urge you can not demand and enjoy sex. Certain factors can generate sexual urge and these factors are finance, joy, physical outlook of the partner and good health. This study is aimed at evaluating the Psychological Factors Determining Lack of Sexual Urge Among Female in South-South Nigeria. This was a descriptive study involving 250 female of reproductive age who were within the age of 18 to 47 years. A well-structured questionnaire was administered to participants. Each participant had one questionnaire to fill appropriately and independently after instructions were given to them by the Research Assistants. The study lasted for a period of 3 months (June to August, 2024). Exclusion criteria were those women that have not attain reproductive age. Inclusion criteria are women that have once experienced sexual urge. Data was analyzed with SPSS version 26 and P value < 0.05 was considered significant. The study reveals that most (40.00%) of the participants were 33-37 years of age, 76.00% were passing through stress, 80.00% were depressed, 76.00% have anxiety, 60.00% are divorcee, 85.71% of their partners had halitosis, 60.00% academic failure, and 80.00% have previous heart brake.
Keywords: Psychological Factors; Determining; Lack; Sexual Urge